Emulsification and application of a thymol loaded antibacterial fatliquor for leather industry. (September 2021) - Yorgancioglu, Ali
In this study, the antibacterial fatliquor emulsion was prepared from castor oil bearing thymol (1, 2, 4 and 8% w/w) to be used in the leather production. The average particle size and zeta potential of the fatliquors were determined by zeta sizer. The thermogravimetric behaviors of fatliquor emulsions under dry air were analyzed in order to determine the weight losses when they are exposed to constant heating rate. After the emulsification process, fatliquor emulsions were applied into chrome tanned cattle leathers. Antibacterial activities of the fatliquored leather were tested according to standard test method for determining the antimicrobial activity under dynamic contact conditions against Gram-positive and Gram-negative bacteria. Minimum inhibitory concentration (MIC) analysis of emulsion was also determined. The bacterial reduction was measured as 99.9% against S. aureus and 98.6% against E. coli bacteria. MIC values obtained from emulsions against bacteria were determined as 6.25 μL/mL and 12.5 μL/mL respectively. The results of antibacterial tests showed that thymol was very efficient in the fatliquor emulsion against both Gram-positive bacteria and Gram-negative bacteria. Physical characterization of leather was also carried out with optimum fatliquor emulsion (4% thymol w/w) and the results showed satisfactory physical properties on the fatliquored leathers compared to similar leather made with commercially available fatliquors. The results of the study indicated that thymol loaded fatliquor emulsions with small particle size could be a promising solo fatliquor to provide functional properties such as physical, strength, morphological and antibacterial properties to leather as an efficient fatliquor compared to conventional fatliquors.